El caminant de la terra: els primers llibres de viatge de Josep M. Espinàs - Gregori, Carme (Caplletra. Revista Internacional de Filologia, 2000)
Resum: Travel books have outstanding protagonism in the Spanish literature of the 1950s and 60s because of their aptness for the prevailing objective that “reality must be told”. The influence of C. J. Cela’ s model and the special conception of the genre in Flistorical Realism constitute the two main axes on which the production develops. José M. Espinás’ first two books, «Viatge al Pirineu de Lleida» («Journey to the Pyrenees of Lleida», 1957) i «Viatge al Priorat» («Journey to the Priorat», 1962), are placed within this reference frame: the former is in the line opened up by Cela with his «Viaje a la Alcarria» («Journey to the Alcarria»), and the latter is closer to the interest for social and economic realism as defended by Social Realism, although without its charactersitc critical intentionality. Paraules clau: llibres de viatges; literatura anys cinquanta i seixanta; Camilo José Cela; Josep M. Espinàs; realisme social